Boosting Recovery During Sleep by Means of Auditory Stimulation - Krugliakova, Elena; Skorucak, Jelena; Sousouri, Georgia; Leach, Sven; Snipes, Sophia; Ferster, Maria Laura; Da Poian, Giulia; Karlen, Walter; Huber, Reto (Frontiers in Neuroscience, 2022)
Sufficient recovery during sleep is the basis of physical and psychological well-being. Understanding the physiological mechanisms underlying this restorative function is essential for developing novel approaches to promote recovery during sleep. Phase-targeted auditory stimulation (PTAS) is an increasingly popular technique for boosting the key electrophysiological marker of recovery during sleep, slow-wave activity (SWA, 1–4 Hz EEG power). However, it is unknown whether PTAS induces physiological sleep. In this study, we demonstrate that, when applied during deep sleep, PTAS accelerates SWA decline across the night which is associated with an overnight improvement in attentional performance. Thus, we provide evidence that PTAS enhances physiological sleep and demonstrate under which conditions this occurs most efficiently. These findings will be important for future translation into clinical populations suffering from insufficient recovery during sleep.